Diachronic evolution of the language - Щигло, Лариса Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The modern stage of the development of linguistics is characterized by the fact that linguistic scientists are increasingly turning their attention to the historical and historical typological problems of language, primarily due to the need to create a theory that would have a more powerful explant power compared to a clearly limited time frame a synchronous approach to the identification of nature, forms of existence, and even the very essence of linguistic phenomena and processes. The current practice of carrying out linguistic analysis with all conviction showed that the synchronous approach itself, taken in isolation from the diachronic one, was unable to provide an adequate explanation for the facts of various structural and semantic transformations in the language in general, its peripheral and relic phenomena, in particular. The human language is a complex, multifaceted phenomenon, the study of which calls for the application of methods for the analysis of other sciences, since only at the "junction of sciences" one can obtain a new knowledge of the real essence of the object under study. The main focus of research is focused on highlighting the possibility of applying an interdisciplinary (and broader – transdisciplinary) approach to investigating evolutionary processes in the language; substantiation of evolutionary linguistic synergetics in the special direction of philological studiеs; determining the prospects for further scientific research of the system of language in diachrony.